Effects of cognitive and stress management training in middle-aged and older industrial workers in different socioeconomic settings: a randomized controlled study - Gajewski, Patrick D.; Stahn, Catharina; Zülch, Joachim; Wascher, Edmund; Getzmann, Stephan; Falkenstein, Michael (Frontiers in Psychology, 2023)
Introduction The demographic change requires longer working lifetime. However, fear of job loss may lead to chronic stress whereas aging and unchallenging work may accelerate cognitive decline and early retirement. Long-time repetitive work led to impairments of cognitive functions in middle-aged and older employees, as demonstrated in a previous study conducted in a large car manufacturer. In the present study, a training concept was implemented to enhance the cognitive and emotional competence of these employees. Methods A first group of employees received a trainer-guided cognitive training only, whereas a wait list control group received a cognitive training and stress management training. This design was applied in two independent samples separated by one year either during or after a socioeconomically tense situation of the factory. Results In sample 1, with a tense occupational situation, the cognitive training effects occurred with a delay of three months. In contrast, in sample 2, with less critical socioeconomic situation, the training effects occurred immediately and persisted three months later. Stress management training showed reduction of subjectively and objectively measured stress level. Discussion The results indicate that effects of cognitive interventions are diminished under chronic stress which can be reduced after a short stress management training. This leads also to enhanced attention and memory in daily life. In contrast, in Sample 2 with less chronic stress, effects of cognitive training were stronger and persisted at least three months later, whereas stress management training had less impact. This suggests that cognitive learning in occupational settings is only efficient at lower stress levels.